Improving Part-of-Speech Tagging Accuracy for Croatian by Morphological Analysis - Agić, Ž.; Dovedan, Z.; Tadić, M. (Informatica)
Improving Part-of-Speech Tagging Accuracy for Croatian by Morphological Analysis